Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Keberhasilan Belajar Siswa Dalam Pendidikan Agama Islam - Syamsurizal, Oky; Afandi, Muslim; Subhan, Mhd (Universitas Majalengka, 2025)
This study aims to analyze the influence of intrinsic and extrinsic motivation on student learning success in Islamic Religious Education subjects. The method used is library research, by analyzing various relevant literature sources. The results of the study show that intrinsic motivations that arise from within students, such as curiosity and spiritual drive, have a significant impact on active engagement and depth of understanding in learning. In contrast, extrinsic motivations such as praise, appreciation, and grades also contribute significantly especially in arousing students' initial interest in learning. This study concludes that the integration of the two provides optimal results for academic achievement and the formation of students' religious character. These findings emphasize the importance of the role of teachers in designing learning strategies that are able to foster and balance these two types of motivation.